Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Bagian Mesh (Management Environment Safety Health) Pada PT. Nikomas Gemilang Divisi Nike - Ahmad Yusup; Angrian Permana; Dewi Surani (Fakultas Ekonomi dan Bisnis Universitas Prima Graha, 2021)
There are problems that must be fixed at PT. Nikomas Gemilang Serang Nike MESH Division. The problem is the lack of implementation of performance in carrying out tasks so that the work is not immediately resolved in compiling reports based on their responsibilities, currently there are employees who come late when they come to work, lack of attention from the leadership to employees and picky employees they like, So that employees who don't get attention feel ignored. This study aims to determine: the effect of work motivation on employee performance, the effect of work discipline on employee performance, the effect of work motivation and work discipline on employee performance at PT. Nikomas Gemilang Serang Nike MESH Divisio. This research method uses an associative quantitative method with causality. The population and samples used in this study were employees at PT. Nikomas Gemilang Serang Nike MESH Division, which has 56 employees. The sampling technique in this study uses a saturated sample where all the population is sampled. The results of this study indicate that: 1. There is a positive and significant effect of work motivation on employee performance. 2. There is a positive and significant effect of work discipline on employee performance. 3. There is a positive and significant effect of work motivation and work discipline together on employee performance at PT. Nikomas Gemilang Serang Nike MESH Division.